ECOLOGICAL SUBSTANTIATION OF CONTROL MEASURES AGAINST HORSEFLIES (DIPTERA, TABANIDAE) IN THE STEPPE ZONE OF NORTH-EASTERN KAZAKHSTAN (ҚазҰУ хабаршысы. Экология сериясы, 2025)
The largest livestock-breeding region of our country is the north-east of Kazakhstan. In order to ensure veterinary well-being of the region and profitability of livestock development, it is important to solve a number of situational tasks. In conditions of sharp-continental climate of the north-east of Kazakhstan one of the main aspects of development, preservation and increase of productivity of cattle population is the most common measures to minimize the damage caused by blood-sucking two-winged insects, including horseflies. As a result of the conducted studies, it was revealed that in the season of insect activity milk productivity of cattle decreased up to 30%, and loss of live weight of young cattle varied from 25% to 40% per day when attacked by dominant species of horseflies. As a result of conducted researches in Pavlodar Priirtyshye 27 species of horseflies belonging to 5 genera were identified. Faunistic complex of the region is represented by European, Turkestan, Mediterranean, Mongolian and Central Asian groups, with predominance of boreal species. The highest species diversity and population density were observed in intrazonal landscapes of the middle Yertis floodplain. Two peaks of mass activity of horseflies have been established: in June and July, which is caused by irregularity of their departure. The main places of occurrence are floodplain lakes, channels and swamps. The activity of gadfly attacks is determined by climatic conditions, with the main influence of temperature and light intensity. The obtained data on seasonal and daily activity of horseflies can be used to develop effective measures to control their mass species.Keywords: Entomology, horseflies, bloodsucking two-winged, gnus, livestock, insects, control measures, insecticides